2006
DOI: 10.1177/1479972306070069
|View full text |Cite
|
Sign up to set email alerts
|

The relation between measures of health status and quality of life in COPD

Abstract: Because quality of life (QoL) and health status (HS) scales contain different kinds of items and are shown not to be equivalent, there is a recommendation to use both types of scales. We investigated the relationship between either type of scale but focusing on the subscales of HS measures. A sample of chronic obstructive pulmonary disease (COPD) patients completed two QoL scales and two HS scales (BPQ and SGRQ), neuroticism, six-minute walk test and FEV1. Factor analysis revealed a two-factor structure (consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
16
0
2
Order By: Relevance
“…Persons with COPD experience progressive declines in pulmonary function and physical capacity along with worsening symptoms and episodic exacerbations; these are often associated with symptoms of depression and worsening mental health status. [1][2][3] The disease has no cure and current treatment does not alter its progression; therefore, treatment largely focuses on symptom management and improving quality of life (QOL). 4 For these reasons, it has become increasingly important to examine the perceived effect of the disease on an affected person's QOL using a health-related quality of life (HRQOL) measure.…”
mentioning
confidence: 99%
“…Persons with COPD experience progressive declines in pulmonary function and physical capacity along with worsening symptoms and episodic exacerbations; these are often associated with symptoms of depression and worsening mental health status. [1][2][3] The disease has no cure and current treatment does not alter its progression; therefore, treatment largely focuses on symptom management and improving quality of life (QOL). 4 For these reasons, it has become increasingly important to examine the perceived effect of the disease on an affected person's QOL using a health-related quality of life (HRQOL) measure.…”
mentioning
confidence: 99%
“…Numerous studies conducted worldwide confirm the fact that shortness of breath and reduced exercise capacity [14,15,16,17,18,19,20,21] are among the symptoms that substantially reduce the quality of life of the ill. Moreover, the level of disease severity leads to a poorer quality of life [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies comparing short-term and long-term effects of pulmonary rehabilitation on the quality of life of patients with COPD (15) using the BPQ and two other widely used disease-specific questionnaires for patients with respiratory disease, i.e., the CRQ and the SGRQ, demonstrated that the instruments were responsive to pulmonary rehabilitation. (16) These results show that the BPQ can also be a valuable instrument in monitoring HRQoL in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%